KURIKULUM PENDIDIKAN TINGGI DI ERA GLOBALISASI (PERGESERAN DARI KURIKULUM INTI DAN INSTITUSIONAL KE KURIKULUM BERBASIS KOMPETENSI) - Febriyanti Febriyanti (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
Higher Education is a strategic economic engine as it plays a key role in the development and application of knowledge, expertise, skills and noble values of society through the development of the society with intensive knowledge to establish a civilized and independent society.One of the goals of education arranged by any institutions is to provide and produce graduates who have the ability and competitiveness in the search, acquisition, and creation of jobs. On the issue of competitiveness, unfortunately the condition of human resources (HR) in Indonesia is at a low level. One reason for the low competitiveness is lies on the higher education curriculum which is based on the content (content-based) that focuses on achievement (GPA) which describes the cognitive aspect, not on competence.One of the changes that must be done is to change the curriculum. Competency Based Curriculum (CBC) is believed to be the best answer to the changing times for the provision of education. Even, the curriculum is an answer to the nation in order to achieve a competitive advantage in the world (nation competitiveness).